2014
DOI: 10.1117/1.jbo.19.3.036022
|View full text |Cite
|
Sign up to set email alerts
|

Coregistered autofluorescence-optical coherence tomography imaging of human lung sections

Abstract: Autofluorescence (AF) imaging can provide valuable information about the structural and metabolic state of tissue that can be useful for elucidating physiological and pathological processes. Optical coherence tomography (OCT) provides high resolution detailed information about tissue morphology. We present coregistered AF-OCT imaging of human lung sections. Adjacent hematoxylin and eosin stained histological sections are used to identify tissue structures observed in the OCT images. Segmentation of these struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The strong AF signal on the right of the AF map due to the cartilage band just under the luminal surface confirms that cartilage produces larger autofluorescence signal. This is consistent with the results on ex vivo human airway sections presented in [43].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The strong AF signal on the right of the AF map due to the cartilage band just under the luminal surface confirms that cartilage produces larger autofluorescence signal. This is consistent with the results on ex vivo human airway sections presented in [43].…”
Section: Resultssupporting
confidence: 82%
“…Higher AF signals correspond to the areas with higher fluorophore concentrations. Cartilage and dense connective tissue include high concentrations of highly fluorescing collagen and elastin fibers [43]. Therefore, we expect that the regions with strong AF signal include cartilage and dense connective tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, some authors have demonstrated the effectiveness of the OCT in combination with AFB to distinguish invasive cancer from CIS and dysplasia from metaplasia, hyperplasia, or normal tissue, using the quantitative measurement of the epithelial thickness (38,39). Furthermore Pahlevaninezhad et al recently reported the combination of Doppler OCT with AFI in 31 patients to guide and improve biopsy of pulmonary nodules, resulting a powerful tool to evaluate pulmonary parenchyma as well (40).…”
Section: Oct Is a Non-invasive Optical Imaging Technique Based Onmentioning
confidence: 99%
“…Combinations of OCT and fluorescence imaging techniques have been developed and applied to various tissues such as the coronary artery [50,51], colon [52][53][54][55], bladder [56], lung [57] and oral cavity [11,58]. Other multimodal approaches for oral cavity detection include combinations of FLIM and reflectance confocal microscopy (RCM) [59], white light imaging and autofluorescence imaging [60], FLIM, UBM, and photoacoustic imaging (PAI) [61], and OCT and RCM [62].…”
Section: Introductionmentioning
confidence: 99%